America as Seen by a Frenchman - Reichenbach, François; Grignon, Marcel; Ripert, Jean-Marc; Sutter, Jérôme (Arrow Academy, 2020)
At the end of the 1950s, celebrated French documentarian François Reichenbach (F for Fake, Portrait: Orson Welles), whose lens captured the likes of Brigitte Bardot and Johnny Hallyday, spent eighteen months travelling the United States, documenting its diverse regions, their inhabitants and their pastimes. The result, "America as Seen by a Frenchman", is a wide-eyed perhaps even naïve journey through a multitude of different Americas, filtered through a French sensibility and serving as a fascinating exploration of a culture that is both immediately familiar and thoroughly alien. [www.amazon.co.uk]